Multiple independent records of local glacier variability on Nuussuaq, West Greenland, during the Holocene - Schweinsberg, Avriel D.; Briner, Jason P.; Licciardi, Joseph M.; Bennike, Ole; Lifton, Nathaniel A.; Graham, Brandon L.; Young, Nicolás E.; Schaefer, Joerg M.; Zimmerman, Susan H. (Quaternary Science Reviews, 2019)
The sensitivity of mountain glaciers to small-scale climate fluctuations makes records of their past extent among the best proxies for identifying spatio-temporal climate variability. Here we build on the few existing Holocene records of local glacier change in Greenland by using three independent geochronological methods—proglacial lake sediment analysis, cosmogenic 10Be surface-exposure dating, and in situ 14C burial modeling—to reconstruct continuous records of Holocene glacier variability on Nuussuaq, West Greenland. 10Be ages of perched boulders indicate eastern Nuussuaq was deglaciated between ∼11.0 and 10.5 ka. Radiocarbon-dated sediments from two lakes on Nuussuaq contain mineral-rich layers between ∼9.6 and 9.0 and ∼8.7–8.0 cal ka BP that may be correlative with nearby ice sheet moraines deposited in the early Holocene. Multiple proxies for glacier size indicate frequent, high-amplitude glacier fluctuations superimposed on net glacier growth during the late Holocene, with significant ice expansion phases at ∼3.7 ka, 2.8 ka, and throughout the past ∼2 ka. Mean 10Be ages from five nested moraine crests confirm that local glacier extents on Nuussuaq culminated during both the Little Ice Age [∼1470 C.E. (n = 3) and 1750 C.E. (n = 3)] and the preceding centuries (∼520–1320 C.E.; n = 11). Results reveal that local glaciers on Nuussuaq episodically advanced and retreated at centennial timescales throughout the Holocene, most likely in response to regional climate changes in West Greenland superimposed on the progressive insolation-driven cooling trend in the Northern Hemisphere. Our new 10Be moraine chronologies coupled with other glacier-size proxies corroborate an emerging pattern of significant summer cooling and glacier expansion in the centuries prior to the Little Ice Age in the Arctic.
Keywords: Cosmogenic 10Be; Cosmogenic in situ 14C; Greenland; Holocene; lake sediment; Mountain glaciers; Neoglaciation

Holocene mountain glacier history in the Sukkertoppen Iskappe area, southwest Greenland - Schweinsberg, Avriel D.; Briner, Jason P.; Miller, Gifford H.; Lifton, Nathaniel A.; Bennike, Ole; Graham, Brandon L. (Quaternary Science Reviews, 2018)
Mountain glaciers and ice caps (GIC) independent of the Greenland Ice Sheet respond rapidly to climate variations and records of their past extent provide information on the natural envelope of climate variability. Here, we use a multi-proxy approach that combines proglacial lake sediment analysis, cosmogenic nuclide surface-exposure dating (in situ 10Be and 14C), and radiocarbon dating of recently ice-entombed moss to generate a centennial-scale record of Holocene GIC fluctuations in southwestern Greenland. Following local deglaciation ∼10-9 ka, sediments from proglacial Crash Lake record a glacier advance at ∼9 ka that is indistinguishable from nearby ice sheet moraines, implying a synchronous response of GIC and the Greenland Ice Sheet to a centennial-scale climate event. Following this local glacier advance, GIC experienced net recession until ∼4.6 ka. Radiocarbon ages of in situ moss (n = 29) and Crash Lake sediments reveal intervals of glacier expansion at ∼1.8, 1.2 and 0.7 ka that are superimposed on an overall trend of net glacier expansion throughout the late Holocene. In situ 14C concentrations from bedrock adjacent to radiocarbon-dated moss samples further constrain the duration of ice cover through the Holocene in this region. We find that our glacier-size proxy records during the past ∼4 ka are broadly consistent with relatively lower temperatures recorded in GISP2 and occur during, or following, intervals of volcanic perturbations. Thus, we speculate that volcanic activity, although less frequent and intense than in the early Holocene and during the Little Ice Age, may have led to centennial-scale variability imprinted on net glacier expansion due to decreasing summer insolation through the late Holocene.
Keywords: Cosmogenic in situ 14C; Glacier fluctuations; Greenland; Holocene; lake sediment; Neoglaciation